LncRNA NONHSAT114552 Sponges miR-320d to Promote Proliferation and Invasion of Chordoma Through Upregulating NRP1 - Zhang, Kai; Liu, Zixiang; Tang, Yingchuang; Shao, Xiaofeng; Hua, Xi; Liu, Hao; Yang, Huilin; Chen, Kangwu (Frontiers in Pharmacology, 2021)
Chordoma is a relatively rare malignant bone tumor with high local recurrence. To date, the mechanism remains unclear. lncRNAs play a pivotal role in tumorigenesis by acting as competitive endogenous RNAs of microRNAs. However, the biological role of lncRNA is still unclear in chordoma. In this research, our aim is to investigate the roles and regulation mechanisms of lncRNA NONHSAT114552 in chordoma development. The expression level of NONHSAT114552 and miR-320d in chordoma tissues was determined by qRT-PCR. Meantime, the correlation between NONHSAT114552 and clinical prognosis was also studied. Bioinformatics analysis and luciferase reporter assays were used to verify the relationship between NONHSAT114552 and miR-320d, and between miR-320d and Neuropilin 1 (NRP1). In addition, effects of NONHSAT114552 on chordoma cells (U-CH1 and U-CH2) proliferation and invasion and its regulation on miR-320d were also evaluated. Furthermore, the influences of NONHSAT114552/miR-320d/NRP1 axis on chordoma tumorigenesis were investigated in vivo. NONHSAT114552 was overexpressed while miR-320d was down-regulated in chordoma tissue compared to fetal nucleus pulposus. Kaplan-Meier survival analysis showed that NONHSAT114552 overexpression was associated with patients’ poor prognosis. Knockdown of NONHSAT114552 significantly suppressed chordoma cell proliferation and invasion. In vitro studies confirmed that NONHSAT114552 acted as ceRNA to regulate NRP1 by directly sponging miR-320d, thus facilitating chordoma cell proliferation and invasion. In vivo study demonstrated that NONHSAT114552 moderated chordoma growth by sponging miR-320d to regulating NRP1. Our findings indicate that lncRNA NONHSAT114552 exhibits a critical role in the tumorigenesis and development of chordoma and it may become one potential prognostic marker and therapeutic target for this disease. .